English Language Learning Strategies of Malaysian Secondary School Students: Implication for Inter-Cultural Communication - Babikkoi, Mallam Adamu; Razak1, Binti Abdul; Zainab, Noor (Scientific Research Publishing, 2014)
English is unquestionably the contemporary language of science, technology, commerce, intercultural communication and scholarship. It is consists of accomplished growing importance in the world. Consequently, in Malaysia concerned parents, researchers, scientists and instructors that know the inevitable impact English language possess over the academic and socio-economic progress of the students clamour for English proficiency. In Malaysia, English is not only the second language in importance but also a school and college subject, and language of instruction of science and mathematics. Interestingly, ESL/EFL studies nowadays are devoted to finding out techniques employed by learners. It is against this backdrop that this study was carried out to discover strategy use among ESL students in Malaysian secondary schools to look further at the implication of their strategy use with regards to inter-cultural communication. Oxford’s SILL Questionnaire was administered to 180 secondary school students and SPSS 7.0 version was used for analysis. Findings reveal the dominance of indirect learning techniques, meaning high anxiety, dependence heavily on peers and teachers to learn English and fewer practice of the oral language. The study recommends the teaching of learning techniques to students and positive exploitation of core-curricular activities that will create and sustain constant practicing of English language among students to facilitate inter-cultural communication.
Keywords: Malaysian Secondary School Students; Inter-Cultural Communication; Language Learning Strategies